1997
DOI: 10.1051/jp4:19971293
|View full text |Cite
|
Sign up to set email alerts
|

Magnetooptical Properties of Ce-Doped YIG Single Crystals

Abstract: The Faraday rotation (FR) of cerium substituted yttrium iron garnets single crystals Ys,C+Fe>On (YIG:Ce) with x=0.055 has been investigated at 1152 and 632.8 nm in the 6 K-600 K temperature range and magnetic field up to 20 kOe applied along the [Ill] and [loo] directions. In contrast to magnetic roperties, the FR of MG.Ce is strongly different fiom FR of pure MG at both wavelengths. The FR contribution of the Cegf ions, mainly attributed to intra-ionic electric dipole transitions between the 4P and 4P 5d1 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…This indicated that the presence of Ce enhanced the formation of YIG phase. This is in agreement with Uniyal and Yadav work's [21]. They found that the substitution with moderate amount of rare earth ions could eliminate or transform the impurity phase of YIP to YIG.…”
Section: Antenna Configurationsupporting
confidence: 91%
See 1 more Smart Citation
“…This indicated that the presence of Ce enhanced the formation of YIG phase. This is in agreement with Uniyal and Yadav work's [21]. They found that the substitution with moderate amount of rare earth ions could eliminate or transform the impurity phase of YIP to YIG.…”
Section: Antenna Configurationsupporting
confidence: 91%
“…To date, various dopants (e.g. La, In, Sr, Sn, Sc, Si) are found to have shown significant magnetic properties of YIG [19][20][21]. However, no One of the possible dopants that could be used for this purpose is CeO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Equation (1) and Fig. 1a-c are crucial for understanding the operating principle of this device; therefore, we highlight a few important features: (1) reversing the current (that is, flipping the in-plane magnetic field in Ce:YIG) changes the sign of Δn eff ; (2) the effective index change differs for the clockwise (CW) and counterclockwise (CCW) propagating modes, having the same amplitude but opposite signs (non-reciprocal effect); (3) the effective index change is the largest when the optical mode is polarized along the y axis (transverse-magnetic polarized mode); (4) the value of the effective index change is proportional to the Faraday rotation constant (Supplementary Section 1), which is expected to increase with decreasing temperature 17,26 .…”
Section: An Integrated Magneto-optic Modulator For Cryogenic Applicat...mentioning
confidence: 99%
“…As reported in Supplementary Section 3.4, Ce:YIG becomes magnetically harder at lower temperatures and a 110 mA electrical current (1.5 mT magnetic field) is not sufficient to magnetically saturate it. Although the Faraday rotation of Ce:YIG is expected to increase for decreasing temperatures 17,26 , a higher magnetic field is needed to reach such a value because of the stronger coercive force that limits the MO split at 77 and 4 K compared with the room-temperature case.…”
Section: Device Performance At Cryogenic Temperaturesmentioning
confidence: 99%
“…However, investigation of the temperature-dependence of the MO and magnetic properties of Ce:YIG is limited and mostly focused on bulk materials. [21][22][23][24] Temperature-dependent studies of bulk Ce:YIG demonstrate an increase of saturation magnetization 22 and Faraday rotation 21 upon cooling which is well approximated by a linear function in the regime from room temperature (RT) to liquid nitrogen temperature. There are little data on magnetocrystalline anisotropy or magnetostriction of Ce:YIG, but rare earth iron garnets typically show a monotonic increase of the magnetocrystalline anisotropy by a factor of 5-50 and an increase in magnetostriction coefficients by a factor of 2-5 when cooled down from RT to liquid nitrogen temperatures.…”
mentioning
confidence: 99%